Competence-Based Education and Training model and its infusion into learning activities at one polytechnic in Zimbabwe - Patrick Chisango Rusike; Pinias Chikuvadze; Joseph Zuva (Eureka: Journal of Educational Research, 2024)
This study sought to gain an understanding concerning how the targeted polytechnic was infusing the Competence-Based Education and Training (CBET) model was into its learning activities. The quantitative approach guided data collection, analysis and interpretation. A semi-structured questionnaire was used to source data from the 18 respondents who were selected through stratified random sampling technique. The collected data was presented using tables and percentages, and analyzed statistically. From the analyzed data it was noted that CBET was conceptualized as a pedagogical model that entailed the designing learning materials, their implementation and assessment. The respondents acknowledged the model’s contribution towards the acquisition of competences by the students under the guidance of the lecturers/instructors at the polytechnic and workplace industry and commerce. It was further noted that mostly student-centered approaches were used in learning activities with the aim to enhance hands-on approach to the acquisition of the competences. It can be concluded that through the respondents acknowledged the relevance of CBET model in learning activities and various approaches were used to infuse in activities that were enhancing students’ acquisition of knowledge, and skills. Based on the above conclusion, the researchers recommend that lecturers be inducted on how best this model can be infused in their learning activities.